Inflammatory pseudotumor of the maxillary sinus in a 15-year-old boy. - Maldjian, J A; Norton, K I; Groisman, G M; Som, P M (American Journal of Neuroradiology, 1994)
Inflammatory pseudotumor is a benign neoplasm composed of fibroblasts, histiocytes, and inflammatory cells. Its occurrence in the paranasal sinuses is rare. We report a case of a 15-year-old boy with a maxillary sinus inflammatory pseudotumor that simulated an aggressive neoplasm on CT scan.